Acrylamide- A Potent Threat in Fried and Baked Food Products - Marimuthu, Manivannan; Chattopadhyay, Kasturi; Vishnupriya, M. S. (Chronicle of Bioresource Management, 2024)
Acrylamide, a process-induced food toxicant, has received wide attention in recent years due to its neurotoxic, genotoxic, and reproductive-toxic effects. It also acts as a potentially carcinogenic compound for humans. It is an unsaturated amide that is easily absorbed by animals and humans after ingestion and distributed in different organs such as the thymus, heart, brain, liver, and kidney. It functions as a precursor in the development of other compounds, such as glycidamide (carcinogen). It has been formed during Maillard reactions, mainly between the reactions of asparagine and reducing sugars at high temperatures. The carbonyl groups of reducing sugars and the amine group of amino acids react to form a Schiff base, leading to the formation of acrylamide. The addition of chitosan is an excellent alternative for achieving this goal because of its richness in amino groups, which interfere with the Maillard reaction that unleashes the formation of acrylamide.